2020
DOI: 10.1371/journal.pone.0236934
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalemia is frequent and has prognostic implications in stable patients attending the emergency department

Abstract: Background Potassium disturbances are associated with adverse prognosis in patients with chronic conditions. Its prognostic implications in stable patients attending the emergency department (ED) is poorly described. Aims This study aimed to assess the prevalence of dyskalemia, describe its predisposing factors and prognostic associations in a population presenting the ED without unstable medical illness. Methods Post-hoc analysis of a prospective, cross-sectional, multicenter study in the ED of 11 French acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
10
0
2
Order By: Relevance
“…It has been reported that 17% of patients with severe hypokalemia died during hospitalization 8 . An increase in short‐term in‐hospital mortality has been reported for patients with hypokalemia 21,22 . It is unclear whether severe hypokalemia itself has an independent impact on patient outcomes; however, potassium is an important determinant of myocardial function, and severe hypokalemia can lead to arrhythmia and sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that 17% of patients with severe hypokalemia died during hospitalization 8 . An increase in short‐term in‐hospital mortality has been reported for patients with hypokalemia 21,22 . It is unclear whether severe hypokalemia itself has an independent impact on patient outcomes; however, potassium is an important determinant of myocardial function, and severe hypokalemia can lead to arrhythmia and sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…8 An increase in short-term in-hospital mortality has been reported for patients with hypokalemia. 21,22 It is unclear whether severe hypokalemia itself has an independent impact on patient outcomes; however, potassium is an important determinant of myocardial function, and severe hypokalemia can lead to arrhythmia and sudden cardiac death. The exact cause of death for patients who experienced cardiac arrest was unknown; however, severe hypokalemia may have triggered the sudden death of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Hypokaliämie ist definiert als eine Kaliumkonzentration von unter 3,5 mmol/l [11,12], wobei ab einer Konzentration von unter 2,5 mmol/l lebensbedrohliche Zustände eintreten können. Ursächlich für eine Hypokaliämie ist entweder eine reduzierte Aufnahme oder sehr viel häufiger eine erhöhte Kaliumausscheidung.…”
Section: Hypokaliämieunclassified
“…However, significant deficiency (<3 mmol/L) or elevations (>6.5 mmol/L) in plasma potassium may cause life-threatening cardiac arrhythmias and sudden death 1. Unsurprisingly, therefore, within the emergency department both hyperkalaemia and hypokalaemia have been associated with risk for both admission to hospital and mortality 3–6…”
Section: Introductionmentioning
confidence: 99%
“… 1 Unsurprisingly, therefore, within the emergency department both hyperkalaemia and hypokalaemia have been associated with risk for both admission to hospital and mortality. 3–6 …”
Section: Introductionmentioning
confidence: 99%